Kiprah Komando Pasukan Sandhi Yudha dalam Operasi Militer di Indonesia Tahun 1971-1985 - Septian Minurdin (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
Research’s background in this study was to investigate Indonesia’s Special Forces formation and military operation conducted by Indonesia Special Forces. After the Proclamation of Independence. Indonesia had no official military forces. At that time, military forces were derived from former independence fighters with a non-formal organization. Indonesia absolutely needed the military forces since the country encountered an attempts of disintegration namely rebellion in many provinces. After military forces established, Indonesia apparently could not overcome the domestic issue, therefore it was very essential to form Special Forces that could conduct military operation more effectively and efficiently. Problem formulation in this research is “how was the role of Sandhi Yudha Forces Command in conducting a military operation in Indonesia from 1971 to 1985?”. The study used the historical method, with four research procedure that are heuristic, critic, interpretation, and historiography. Moreover, literature study by analysed relevant sources was applied. The study research revealed, Firstly, Indonesia’s Special Forces was formed owing to the needs of a military operation in coping rebellions after Indonesia’s independence. Secondly, after the formation, Indonesia’s Special Forces has undergone numbers of re-organization that aim to improve the needs and system organization. These act as an effect from the development of forces and country ability in funding Special Forces' institution. Thirdly, after re-organization process between 1971 to 1985, Indonesia’s Special Forces has conducted numbers of combat and non-combat military operations, such as Valey X Expedition in West Irian, the quell of Communist Group in West Kalimantan and Hostages' Rescuing Operation of Garuda Airline DC-9-WOYLA in Don Muang Airport, Thailand